Application of petai peel as an iron corrosion inhibitor in sodium chloride medium. Issue 1 (March 2021) - Tambun, R; Sidabutar, D H; Alexander, V
Abstract: Tannin as an organic inhibitor has been proven capable as a metal inhibitor in acidic media. The purpose of this study is to test the tannin ability of the Petai peel to inhibit the iron plate in the sodium chloride solution. The inhibitory ability of tannins derived from the Petai peel will be assessed in the form of powders, concentrated extracts, and pure tannins. Corrosion rate and efficiency of inhibition as tested parameters will be calculated by doing some variations on the immersion time and inhibitor concentration. Based on the results obtained, Petai peel powder, Petai peel concentrated extracts, and tannins from Petai peels can reduce the rate of iron corrosion in sodium chloride solution, but the best inhibitors of these three forms are in the form of tannins, which can reach the lowest corrosion rate of 0.9770 mpy and inhibition efficiency up to 92.86%. The lowest corrosion rate and highest efficiency are obtained by adding tannin as much as 3 g and immersion duration for 3 days.